A Comparative Study to Assess the Knowledge and Attitude of School Going Children Regarding Importance of Personal Hygiene in Selected Rural and Urban Schools of Ludhiana, Punjab - Kaur, Birpal (International Journal of Nursing Research, 2023)
Background: The study’s objectives were to assess the knowledge, attitudes, and relationship between rural and urban school-aged children’s knowledge and attitudes about personal hygiene. Methods: The study used a comparative research design. A stratified random sample selection procedure was utilized. One hundred samples (50 from rural areas and 50 from cities) were selected. The population of the study was rural and urban school going children 9–11 years. To examine the data, descriptive and inferential statistics were employed. Results: The survey concluded that 40% (20) of rural schoolchildren and 44% (22) of urban schoolchildren had strong knowledge. About 96% (48) urban and 88% (44) rural schoolchildren valued personal cleanliness. The mean knowledge score of urban schoolchildren was 19.48, higher than rural children 16.52, and their mean attitude score was 74.18, much higher than rural children 68.10. The mean knowledge score of rural and urban children was statistically significant for age, mother’s education, and source of information, but not for household type or monthly income. In rural children, class was significant while gender was non-significant. The mean attitude score of rural and urban school children was statistically significant for age, gender, class, but not for mother education, type of family, family monthly income, or source of information. Based on the study, rural and urban school children received personal hygiene advice. When feasible, guidelines should be flexible. Conclusion: Children attending schools in urban areas had better knowledge than those attending schools in rural areas, but both groups of students shared a favorable outlook on the value of good personal hygiene.